Job Satisfaction of Military Officers of Royal Thai Armed Forces Headquarters, Chaengwattana. - Yotatip, Narueporn; Klaitabtim, Juthatip (Journal for Developing the Social and Community, 2023)
This research is conducted with the objectives to 1) study job satisfaction level of military officers of Royal Thai Armed Forces Headquarters, Chaengwattana. 2) compare job satisfaction of military officers of Royal Thai Armed Forces Headquarters, Chaengwattana categorized by personal factors. and 3) study work factors that affect Job Satisfaction of Military Officers of Royal Thai Armed Forces Headquarters, Chaengwattana. 350 personnel of Military Officers of Royal Thai Armed Forces Headquarters, Chaengwattana are the sample group in this research. The data collection instrument was questionnaire. The statistics used to analyze data included average, frequency, T-Test, one-way ANOVA, and Multiple Regression Analysis. The level of statistical significance was set at 0.05. The results of the research revealed that the military officers of Royal Thai Armed Forces Headquarters, Chaengwattana there was a high level on the job satisfaction in all aspects. The level of the work factors all aspects at the high level. The hypothesis test showed that the military officers of Royal Thai Armed Forces Headquarters, Chaengwattana with different ranks had a statistically significant difference in job satisfaction with statistically significant at 0.05, and work factors in terms of job characteristics, professional status, recognition, and personal well-being affected job satisfaction of military officers of Royal Thai Armed Forces Headquarters, Chaengwattana with a statistical significance of 0.05.